Pengembangan kurikulum information literacy di perguruan tinggi: Best practices dari beberapa negara maju - Faizuddin Harliansyah (Al Maktabah, 2015)
This article discusses information literacy curriculum (IL) in college. The concept of information literacy translated from researchers IL among others from the American Library Association, ACRL, CILIP, and SCONUL. IL standard model widely adopted by universities around the world, the Seven pillars of information literacy and Information literacy competency standards for higher education. Information literacy framework is a grand strategy for the implementation of the IL program at a university, institution or country. Libraries need to organize IL workshops and training IL that is both classical and also develop material IL that can be accessed online. To develop an IL model / standard appropriate to the Indonesian context, we can start from scratch or adopt the mode /standard that already exists.